Influence of cooling temperature on load-carrying performance of a radial HTS magnetic bearing. Issue 1 (1st May 2022) - Guan, Xiang; Zou, Yincai; Bian, Xing; Shang, Jin; Wu, Jihao; Li, Qing
Abstract: High temperature superconducting (HTS) magnetic bearing can operate in the harsh environment of low temperature and negative pressure with low loss and self-stability. Therefore, it has been gradually applied in flywheel energy storage, cryogenic liquid pump, cold compressor and some other cryogenic rotating machinery. The load-carrying performance of HTS magnetic bearing is affected by the cooling temperature of HTS directly. In this paper, the linear model is used to modify the temperature dependence to evaluate the influence of cooling temperature on load-carrying performance quantitatively, and the results are analyzed and displayed from the aspects of maximum levitation force, levitation stiffness and hysteresis effect. The research results of this paper have practical significance for the design and safe operation of HTS levitation system.